Promouvoir l’égalité en développant l’histoire des femmes et du genre dans l’enseignement secondaire - Cécile Beghin; Véronique Garrigues; Camille Noûs (Genre & Histoire)
Though Mnemosyne has been working on fostering gender equality in schools for over ten years–like many other gender-equality organizations–, France’s national syllabi in History, as proposed since 2010, keep on side-tracking women and largely ignoring gender issues. Yet the law on equality is quite clear and History teachers are essential in promoting equality. Training teachers in gender issues is thus of paramount importance as is the rewriting of History syllabi in France, if we want mind-sets about gender to evolve.